Wettability of the surface of heat-treated juvenile teak wood assessed by drop shape analyzer - de Oliveira Lopes, Juliana; Aparecida Garcia, Rosilei; Miguel do Nascimento, Alexandre (Maderas. Ciencia y Tecnología, 2018)
This study investigated the effect of the heat treatment on the wettability of the surface of juvenile teak (Tectona grandis) wood assessed by drop shape analyzer. Heartwood and sapwood samples were heat-treated at 180 and 200oC. Contact angle measurements were done every 5 s for 120 s using a KRÜSS DSA100. Heartwood had lower wettability than sapwood. Heat-treatment decreased the surface wettability of both heartwood and sapwood, especially in the wood treated at 200oC. Heartwood had lower wettability than sapwood, even after heat treatment.